Ryzykowne zachowania seksualne mężczyzn odbywających karę pozbawienia wolności = Risk sexual behaviours of men serving prison sentences - Łukaszek, Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Risk sexual behaviours are an important element of lifestyle of socially maladjusted persons. This fact is mainly due to the following factors: the specific hierarchy of values of this group of people; dogmatic integration of their attitudes; intoxication and drug addiction; psychopathic personality structure of some of them. Risk sexual behaviours shall be treated as social maladjustment symptoms and therefore should be subject to correctional rehabilitation.
Keywords: convicts` sexuality; risky sexual behaviours; partnership sexual norm; sexual violence; manifestation of prison subculture; seksualność skazanych; ryzykowne zachowania seksualne; partnerska norma seksualna; przemoc seksualna; przejawy subkultury więziennej